2018
DOI: 10.5114/jcb.2018.77949
|View full text |Cite
|
Sign up to set email alerts
|

Five-year effectiveness of low-dose-rate brachytherapy: comparisons with nomogram predictions in patients with non-metastatic prostate cancer presenting significant control of intra- and periprostatic disease

Abstract: PurposeTo assess the effectiveness of low-dose-rate (LDR) brachytherapy in patients with localized prostate cancer and to compare the outcome with predictions from Kattan and Partin nomograms at 60 months after seed implantation.Material and methodsOne thousand, one hundred and eighty-seven patients with localized prostate cancer at low-, intermediate-, or high-risk of progression received LDR brachytherapy using iodine-125 seeds with curative intent, applied as monotherapy or in combination with external beam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 49 publications
(67 reference statements)
0
15
0
1
Order By: Relevance
“…There have been several reports to compare the treatment outcomes and GU or GI toxicities [ 8 , 9 , 10 , 11 , 12 , 13 , 14 ]. However, they included a variety of LDR-BT modalities or sources, or different prescribed doses such as mixed 125 I and 103 Pb [ 8 , 15 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There have been several reports to compare the treatment outcomes and GU or GI toxicities [ 8 , 9 , 10 , 11 , 12 , 13 , 14 ]. However, they included a variety of LDR-BT modalities or sources, or different prescribed doses such as mixed 125 I and 103 Pb [ 8 , 15 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Higher dose can deliver to prostate with lower exposure to organs at risks; 2. The treatment time became remarkably shorter than EBRT because usually the insertion was completed within one day [ 14 , 19 , 27 ]. In comparison with EBRT, LDR-BT can deliver a higher dose with lower exposure to organs at risk.…”
Section: Discussionmentioning
confidence: 99%
“…Once patients with aggressive, high-risk PCa have been identified, therapeutic MCs may be used sequentially for tumour therapy and these MCs could even be delivered intraprostatically during a standard 12-core biopsy. Therapeutic MCs would act as an intermediate treatment post-diagnosis to prevent cancer spreading prior to patients receiving more radical procedures such as prostatectomy or brachytherapy, as these procedures are considerably more effective for early-stage disease [44]. A dual-MC theranostic system allows for separate administration of MCs pre-and post-diagnosis to match their clinical usage, whereas the same would not be possible for an all-in-one theranostic MC as both genes would be administered together.…”
Section: Discussionmentioning
confidence: 99%
“…The 5-year bFFF or bRFS rates using the Phoenix definition were reported to be 92. (12,16,18,19,(24)(25)(26)(27)(28)(29), respectively. In our study, for the low-risk patients, 98.35% of the patients were treated with PI monotherapy and 39.40% of the patients received HT, and their 5-year bFFF rate was 94.9%.…”
Section: Discussionmentioning
confidence: 99%
“…The rate of high-risk patients who received HT was 80.45% in our study. Zimmermann et al reported that the rate of high-risk patients who received HT was 60.4%, and their 5-year bFFF rate was 79.2% in high-risk patients (12). Ohashi et al reported that the rate of high-risk patients who received HT was 49.0%, and their 5-year bFFF rate was 84.8% in high-risk patients (27).…”
Section: Discussionmentioning
confidence: 99%